Educational Attainment and Satisfaction With the Healthcare System: Racial Variation - Shervin Assari (Baqiyatallah University of Medical Sciences, 2020)
Background: As shown by Minorities' Diminished Returns (MDRs), ethnic minorities show weaker than expected effects of education level on health outcomes. However, this pattern is better demonstrated for health behaviors and health care utilization than satisfaction with care. Additionally, more is known about MDRs in African Americans than the Latino population. Thus, there is a need to study MDRs of education on healthcare satisfaction in highly educated African American and Latino individuals. Objectives: We tested ethnic differences in the association between education level and satisfaction with healthcare among American adults. Methods: The National Health Interview Survey (2015) included 24,835 adults who were Latino, non-Latino, African American, or White. The independent variable was education level. The dependent variable was satisfaction with healthcare. Age, gender, marital status, employment, region, physical health (self-rated health, and chronic diseases, body mass index), and mental health (psychological distress) were the covariates. Ethnicity was the moderator. Logistic regression was used for data analysis. Results: Higher education level was associated with higher satisfaction with healthcare in White but not African Americans. In the pooled sample, African American ethnicity showed a significant statistical interaction with education level suggesting a significantly smaller effect of high educational attainment on satisfaction with healthcare for African Americans than White adults. A similar interaction could not be found for Latino ethnicity, suggesting that education similarly enhances healthcare satisfaction for Latino and non-Latino adults. Conclusion: High education level boosts satisfaction with healthcare for Whites but not African Americans.